Techno-Economic Analysis for the Coating of Seeds with Sodium Alginate Plasticized by Glycerol Using the Wurster Fluid-Bed Bottom Spray Process - Bogdan Trică; Alin Enache; Florin Oancea (Chemistry Proceedings)
The seed coating with sodium alginate plasticized by glycerol was simulated in batch mode using SuperPro Designer 10. The effect of changing certain inputs such as the seed size, film thickness, and the price of the seeds on the capital and operating costs was estimated. The process simulation predicts capital costs of EUR 250,000 and annual operating costs of EUR 730,000 for producing 1788 batches of 50 kg of coated seeds with a coating thickness of 50 µm for seeds with a diameter of 6 mm at an initial purchasing price of 5 EUR/kg. The annual operating time is considered to be 8000 h.